FILUM PORIFERA: DARI KEINDAHAN LAUT UNTUK WISATA, EKONOMI LOKAL, HINGGA KESEIMBANGAN EKOSISTEM DI INDONESIA - Chairunnisa; Shupaeroh, Hanna Yasmin; Hibatillah Hasanah; Sipa'us Sa'adah; Zafirah Choirunisyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The phylum Porifera, commonly known as sea sponges, plays a vital role in maintaining marine ecosystem balance and holds significant potential in the tourism and local economic sectors in Indonesia. This study aims to explore the ecological and economic benefits of Porifera, particularly within the context of Indonesia’s rich marine biodiversity. The method employed is a qualitative descriptive literature review, analyzing various relevant studies and data on the presence and utilization of Porifera. The findings indicate that Porifera function as natural biofilters and indicators of marine ecosystem health, while also offering aesthetic value that can be developed as an attraction for marine tourism. Furthermore, several Porifera species contain bioactive compounds with high economic value, making them promising resources for pharmaceutical and cosmetic industries. The sustainable use of Porifera can support marine conservation efforts while enhancing the livelihoods of coastal communities. Therefore, collaboration among government, academia, and local communities is essential for managing this potential wisely and sustainably.